Relative dosimetry with an MR‐linac: Response of ion chambers, diamond, and diode detectors for off‐axis, depth dose, and output factor measurements. Issue 2 (21st December 2017) - O'Brien, Daniel J.; Dolan, James; Pencea, Stefan; Schupp, Nicholas; Sawakuchi, Gabriel O.
Abstract : Purpose: The purpose of this study was to acquire beam data for an MR‐linac, with and without a 1.5 T magnetic field, by using a variety of commercially available detectors to assess their relative response in the magnetic field. The impact of the magnetic field on the measured dose distribution was also assessed. Methods: An MR‐safe 3D scanning water phantom was used to measure output factors, depth dose curves, and off‐axis profiles for various depths and for field sizes between 2 × 2 cm 2 and 22 × 22 cm 2 for an Elekta MR‐linac beam with the orthogonal 1.5 T magnetic field on or off. An on‐board MV portal imaging system was used to ensure that the reproducibility of the detector position, both with and without the magnetic field, was within 0.1 mm. The detectors used included ionization chambers with large, medium, and small sensitive volumes; a diamond detector; a shielded diode; and an unshielded diode. Results: The offset of the effective point of measurement of the ionization chambers was found to be reduced by at least half for each chamber in the direction parallel with the beam. A lateral shift of similar magnitude was also introduced to the chambers' effective point of measurement toward the average direction of the Lorentz force. A similar lateral shift (but in the opposite direction) was also observed for the diamond and diode detectors. The measured lateral shift in the dose distribution was independent of depth and field size for each detector for fields between 2 × 2 cm 2 and 10 × 10 cm 2 . The shielded diode significantly misrepresented the dose distribution in the lateral direction perpendicular to the magnetic field, making it seem more symmetric. The percentage depth dose was generally found to be lower with the magnetic field than without, but this difference was reduced as field size increased. The depth of maximum dose showed little dependence on field size in the presence of the magnetic field, with values from 1.2 cm to 1.3 cm between the 2 × 2 cm 2 and 22 × 22 cm 2 fields. Output factors measured in the magnetic field at the center of the beam profile produced a larger spread of values between detectors for fields smaller than 10 × 10 cm 2 (with a spread of 2% at 3 × 3 cm 2 ). The spread of values was more consistent when the output factors were measured at the point of peak intensity of the lateral dose distribution instead (except for the shielded diode which differed by up to 2% depending on field size). Conclusions: The magnetic field of the MR‐linac alters the effective point of measurement of ionization chambers, shifting it both downstream and laterally. Shielded diodes produce incorrect and misleading dose profiles. The output factor measured at the point of peak intensity in the lateral dose distribution is more robust than the conventional output factor (measured at central axis). Diodes are not recommended for output factor measurements in the magnetic field.